Assessment of equivalence of composite liners. Issue 4 (1st August 2004) - Brachman, R. W. I.; Rowe, R. K.
Abstract : The equivalence of composite liners involving a geomembrane (GM) and a compacted clay liner (CCL) to alternative composite liners with a geomembrane, geosynthetic clay liner (GCL) and attenuation layer (AL) is assessed in terms of the contaminant impact occurring in a receptor aquifer. Calculations of contaminant impact of dichloromethane, benzene and chloride through GM/CCL/AL and GM/GCL/AL composite liners are reported for a hypothetical municipal solid waste landfill. The geomembrane in conjunction with either the CCL or GCL is very effective at controlling leakage such that diffusion essentially dominates the impact on the aquifer for the service life of the geomembrane. The geomembrane itself offers little resistance to diffusion of dichloromethane and benzene, and consequently the CCL or GCL and AL (of suitable thickness) are required to protect the aquifer. In contrast, the geomembrane acts as an excellent diffusion barrier to chloride over its service life. For the cases and parameters examined, the GM/GCL/AL liners were found to provide the same or even greater environmental protection to the underlying aquifer relative to GM/CCL/AL liners provided the total thickness of the liner system with the GCL was the same as that with the CCL. This can be achieved by having a thicker attenuation layer with the GM/GCL liners. Chloride impacted on the aquifer only after the service life of the geomembrane had been reached, after which contaminant transport was controlled by advection though the soil component of the liner for the cases examined.